2021
DOI: 10.1002/ldr.4108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of root‐glomalin on soil carbon storage in trees' rhizosphere and interspace of a tropical dry forest

Abstract: Increasing soil organic carbon (SOC) concentration is a desirable aspect of afforestation. Glomalin‐related soil protein (GRSP) is a ubiquitous component of SOC, preferentially produced by arbuscular mycorrhizal fungi (AMF) during symbiotic association with the plant roots. Although the role of AMF in GRSP production is well established, the role of root in GRSP production is not yet clear. Hence, we aimed to assess the glomalin in different tree roots (i.e., glomalin‐related root protein; GRRP) and its influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 49 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…The study by Guo [99] showed that GRSP played an important function in soil carbon pooling. In addition, many experimental studies suggest that GRSP content is positively correlated with soil organic carbon content and is a key component of soil organic carbon [100][101][102]. Kumar et al [103] found a correlation between GRSP and soil organic carbon accumulation in a study on soils in coal mining areas.…”
Section: Carbon Fixation Functionmentioning
confidence: 99%
“…The study by Guo [99] showed that GRSP played an important function in soil carbon pooling. In addition, many experimental studies suggest that GRSP content is positively correlated with soil organic carbon content and is a key component of soil organic carbon [100][101][102]. Kumar et al [103] found a correlation between GRSP and soil organic carbon accumulation in a study on soils in coal mining areas.…”
Section: Carbon Fixation Functionmentioning
confidence: 99%
“…These plants are important for windbreak, sand fixation, and landscape, which in turn are important for maintenance and stability of mountain and desert ecosystems. To date, most studies have focused on forests, and farmland ecosystems [10][11][12][13] evaluating only the differences in soil organic carbon and aggregate at different elevations in the Helan Mountains [14]. By contrast, few research have been conducted on GRSP.…”
Section: Introductionmentioning
confidence: 99%